Spanning Tree Protocol (STP) Based Computer Network Performance Analysis on BPDU Config Attacks and Take Over Root Bridge Using the Linear Regression Method - Yuliani Indrianingsih; Hero Wintolo; Eviana Yulianti Saputri (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2021)
Spanning Tree Protocol (STP) is used in manageable switch devices that apply more than one path to the connection between switches. This study aims to assist engineer staff in improving STP network security. Furthermore, the benefit is to improve the STP network security system by using the Spanning Tree Protocol and Virtual Local Area Network (VLAN) trunking mitigation techniques. The results of testing data before STP is attacked, after STP attacked, and anticipatory data. Then a simple linear regression analysis is carried out by the result of that there is not a significant relationship between time and size in the DoS attack, which Â 48.6% of the time variable is influenced by the size of Â variable, while Â the remaining 51.4% by other variables. Root attack is 43.8%-time variable is influenced by size variable, the remaining 56.2% by other variables. Correlation between Karl Pearson DoS and root, there is a significant relationship between time and size, with the DoS correlation coefficient (-0.697) in contrast root (-0.662), and paired sample t-test (paired sample t-test) can be concluded the anticipation which is done by using BPDU guard and root guard mitigation.